2006
DOI: 10.1111/j.1442-2050.2006.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in glutathione S-transferases T1, M1 and P1 and susceptibility to reflux esophagitis

Abstract: Recent studies indicate that the prevalence of reflux esophagitis (RE) in China is increasing. RE is one of the most common esophageal complications associated with gastroesophageal reflux disease (GERD) and RE-Barrett's esophagus-esophageal adenocarcinoma (EAC) sequence has been considered as an histogenesis model for EAC in Western countries. RE is only present in a subset of patients with GERD, suggesting an altered susceptibility to RE may exist in these GERD individuals. However, the genetic changes relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
2
15
1
Order By: Relevance
“…Our results, however, are in disagreement with those of a previous study that suggested association between GSTP1 variants (alone or in interaction with H. pylori infection) and susceptibility to reflux esophagitis in the China population (Liu et al 2006). In our study, patients with GSTP1*B allele had no significantly increased risk for development of reflux esophagitis alone.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Our results, however, are in disagreement with those of a previous study that suggested association between GSTP1 variants (alone or in interaction with H. pylori infection) and susceptibility to reflux esophagitis in the China population (Liu et al 2006). In our study, patients with GSTP1*B allele had no significantly increased risk for development of reflux esophagitis alone.…”
Section: Discussioncontrasting
confidence: 57%
“…Although several studies have been undertaken to examine the association between susceptibility to some type of cancer (Morita et al 1998;Tan et al 2000;Lee et al 2000;De Bruin et al 2000) and genetic polymorphism in GSTs, there are limited data on their association with reflux esophagitis (Liu et al 2006). The aim of this study was to analyze associations of the GST polymorphisms with reflux esophagitis and BE, and their interactions with smoking status and H. pylori infection in influencing the susceptibility to develop these complications of GERD in the Czech population.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study by Yu et al [26] was the major source of the heterogeneity in this gene-gene interaction analysis and might have some differences compared to other studies in the selection of controls, or other undefined aspects. For instance, control subjects were selected from HBsAg carriers in the Yu et al study [26] while control subjects in other studies were mainly from healthy controls [18,24,34,35,38,39], and this discordance in the selection of controls among different publications might possibly lead to between-study heterogeneity. Furthermore, meta-regression analysis also suggested that the source of controls might be a major source of heterogeneity in GSTM1-GSTT1 interaction analysis, which further validated the hypothesis above.…”
Section: Discussionmentioning
confidence: 99%
“…These 24 individual case-control studies were published from 1997 to 2009 with 14 in English [19,22,23,[25][26][27]29,30,32,[35][36][37][38]40] and 9 in Chinese [18,20,21,24,28,31,33,34,39]. Table 1 presents a brief description of these 24 case-control studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 98%
“…Individuals homozygous for the null allele lack GST enzyme activity and hence may not be able to detoxify the chemicals [29,30]. However, GSTT1 and GSTM1 polymorphisms may not be associated with risk of GERD, though GSTP1 b allele was associated with susceptibility to GERD [31], especially to BE [32].…”
Section: Gst and Risk Of Gerdmentioning
confidence: 95%